2020
DOI: 10.3390/s20071923
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Robustness of Smartphone Photoplethysmography: A Signal Quality Index Approach

Abstract: Heart rate variability (HRV) provides essential health information such as the risks of heart attacks and mental disorders. However, inconvenience related to the accurate detection of HRV limits its potential applications. The ubiquitous use of smartphones makes them an excellent choice for regular and portable health monitoring. Following this trend, smartphone photoplethysmography (PPG) has recently garnered prominence; however, the lack of robustness has prevented both researchers and practitioners from emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…It is assumed that the spatially averaged intensity signal 𝑦 𝑎𝑣𝑔 (𝑡) is related to a small change in the skin color and would be proportional to the changes in the blood volume in the arteries and capillaries underneath the skin during the cardiac cycle [15,[17][18]. The main problem of this method is its [32] 128 Hz SBP and HR (multimodal PPG and ECG) capability of PPG data sampling is limited to the maximum capture rate fps of the CIS, hence the acquired Fs of 𝑦 𝑎𝑣𝑔 is typically ≤ CIS fps [19][20].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It is assumed that the spatially averaged intensity signal 𝑦 𝑎𝑣𝑔 (𝑡) is related to a small change in the skin color and would be proportional to the changes in the blood volume in the arteries and capillaries underneath the skin during the cardiac cycle [15,[17][18]. The main problem of this method is its [32] 128 Hz SBP and HR (multimodal PPG and ECG) capability of PPG data sampling is limited to the maximum capture rate fps of the CIS, hence the acquired Fs of 𝑦 𝑎𝑣𝑔 is typically ≤ CIS fps [19][20].…”
Section: Related Workmentioning
confidence: 99%
“…Other researchers tried to solve this problem by not focusing on the low-sampling rate problem but instead developing an algorithm that detects and separate clean PPG signal from the noisy ones [21][22][23]. For example, Tabei et al [21], proposed a novel personalized motion and noise artifact detection algorithm using neural network and signal quality index to reduce false positive alarm on atrial fibrillation (AF) detection.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account that the possible HR values ranges from 40 [bradycardia in young users (Kawachi et al, 1995;Longin et al, 2005;Sharma et al, 2015)] to around 220 bpm (which is the maximum HR value in young users or in newborns), a minimum sampling rate of 8 fps should be guaranteed (sampling theorem). However, considering the analysis of heart rate variability (HRV), different studies investigated the minimum sampling frequency (f s ) that should be assured (Choi and Shin, 2017;Liu et al, 2020;Béres and Hejjel, 2021). Authors in (Choi and Shin, 2017) showed that the minimum f s depends on the HRV variables which can be obtained (e.g., f s > 10 Hz for LF/HF, f s > 20 Hz for NN50 and pNN50; see Choi and Shin (2017) for further details).…”
Section: Heart Rate and Other Cardiac Parametersmentioning
confidence: 99%
“…Since life-threatening forms of COVID-19 involve a systemic inflammatory surge similar to sepsis, future HRV assessment in a large cohort of COVID-19 and healthy subjects is worth doing. Indeed, HRV monitoring is now possible not only in intensive care units [135], but also at a populational level due to the wide use of smartphones and both iOS and Android HRV applications [136,137]. Notably, a few years ago, a study suggested that such ambulatory monitoring of heart rate in 43 individuals up to 2 years could allow early sepsis detection with 100% sensitivity [138].…”
Section: Ambulatory Monitoring Of Auricular Vagal Tone Through Heart Rate Variability Provides An Attractive Pre-diagnosis Tool In Covid-mentioning
confidence: 99%